Sodium-ion battery material with lamellar cross-linked structure and preparation method of sodium-ion battery material

By using bimetallic sulfide/sulfur nitrogen co-doped graphene composite in sodium ion battery materials, the sheet crosslinking structure is used to improve the embedding/detachment reaction of sodium ions, the problems of structural collapse and Na+ insertion/extraction rate limiting during the circulation process of existing materials are solved, and high specific capacity, high rate performance and excellent cycling stability are achieved.

CN119627081APending Publication Date: 2025-03-14GUANGXI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411837299.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing sodium ion battery materials are prone to structural collapse during circulation, resulting in rapid attenuation of reversible specific capacity, and the insertion/extraction of Na+ is limited by the slow diffusion rate, resulting in lower power density and poor cycle stability.

Method used

Bimetallic sulfide/sulfur nitrogen co-doped graphene composite material is used to synthesize materials with sheet crosslinked structures through solvothermal and vulcanization treatment methods to improve the agglomeration of molybdenum disulfide and antimony trisulfide, and form a stable heterostructure to improve electrochemical performance.

Benefits of technology

The material improves the embedding/detachment reaction of sodium ions through the sheet crosslinking structure, provides a fast transmission channel, prevents structure collapse, improves sodium storage capacity and structural stability, and enhances specific capacity, rate performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627081A_ABST
    Figure CN119627081A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium-ion batteries, in particular to a sodium-ion battery material with a lamellar cross-linked structure and a preparation method thereof, the sodium-ion battery material is a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material, the molecular formula is MoS2 / Sb2S3 / SNGr, and the sodium-ion battery material has a mutually cross-linked lamellar structure. According to the invention, molybdenum disulfide, antimony trisulfide and sulfur-nitrogen co-doped graphene with a thin-layer structure are synthesized into the bimetallic sulfide / sulfur-nitrogen co-doped graphene sodium-ion battery material with a lamellar cross-linked structure according to a certain proportional relation through a solvothermal and vulcanization treatment method; the bimetallic sulfide and the sulfur-nitrogen co-doped graphene achieve a good synergistic effect, the cycling stability of the material can be well maintained, the sodium storage capacity of the material is increased, and the specific capacity, the rate performance and the cycling stability of the composite material are all improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion battery material with a sheet cross-linking structure and a preparation method thereof. Background Art

[0002] The rapid development of human society has led to the continuous consumption of fossil energy and severe environmental pollution. Therefore, the development of renewable energy and new energy storage battery technology has become a broad consensus in human society.

[0003] Sodium-ion batteries are considered to be a very potential alternative or supplement to lithium-ion batteries due to their abundant sodium resources, high safety and good environmental protection. In order to obtain sodium-ion batteries with high energy density, researchers have conducted extensive and in-depth research on negative electrode materials. Metal sulfides have the advantages of abundant raw materials, low cost and high theoretical capacity, and show great commercial application potential in energy storage and energy conversion. Among them, molybdenum disulfide and antimony trisulfide have unique layered structures, which are conducive to the insertion / extraction reactions of sodium ions and can provide fast transmission channels for ions. However, in actual applications, due to the huge volume effect of molybdenum disulfide and antimony trisulfide, structural collapse is prone to occur during the cycle, which ultimately leads to a rapid decay of the reversible specific capacity of the battery. In addition, Na in metal sulfides + The insertion / extraction of ions is limited by their slow diffusion rate, resulting in low power density and poor cycling stability.

[0004] Therefore, how to overcome these shortcomings and make full use of the advantages of metal sulfides is the key to developing sodium-ion battery materials with high specific capacity, high rate performance and high cycle stability, which is of great significance for breaking through the application bottleneck of materials and accelerating the commercial application of materials. Summary of the invention

[0005] The object of the present invention is to provide a sodium ion battery material with a sheet cross-linked structure and a preparation method thereof in order to solve the above-mentioned problems.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: providing a sodium ion battery material with a cross-linked sheet structure, wherein the sodium ion battery material is a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material with a molecular formula of MoS2 / Sb2S3 / SNGr, and the sodium ion battery material has a mutually cross-linked sheet structure.

[0007] In addition, the present invention also provides a method for preparing the above-mentioned sodium ion battery material with a cross-linked sheet structure, comprising the following steps:

[0008] (1) taking a molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, adding deionized water and / or ethanol, and dispersing evenly to obtain a solution A; wherein in the molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, the sulfur-nitrogen co-doped graphene accounts for 8%-15%;

[0009] (2) taking antimony acetate, antimony chloride and / or antimony nitrate, adding them to deionized water or a mixture of ethanol and deionized water, and dispersing them uniformly to obtain a solution B; wherein the volume ratio of ethanol to deionized water in the mixture of ethanol and deionized water is 1:1;

[0010] (3) 1,10-phenanthroline is taken and added to a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; the mixture is dispersed uniformly to obtain a solution C;

[0011] (4) adding the solution B obtained in step (2) to the solution C obtained in step (3) and dispersing them evenly to form a solution D;

[0012] (5) adding the solution A obtained in step (1) above to the solution D obtained in step (4), and adding deionized water and / or ethanol to make up the volume to form a solution E;

[0013] (6) drying solution E to obtain a solid powder;

[0014] (7) placing the dried solid powder in a tube furnace, introducing a protective gas, calcining under a protective gas environment, and cooling to room temperature after the calcination to obtain a precursor MoS2 / SNGr-Sb;

[0015] (8) placing thiourea or sulfur powder in a first calcined boat, placing the precursor MoS2 / SNGr-Sb in a second calcined boat, placing the first calcined boat and the second calcined boat in a tube furnace, wherein the first calcined boat is located on the side close to the protective gas introduction;

[0016] (9) introducing a protective gas, performing a sulfurization treatment in the protective gas, and then cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material.

[0017] In the above preparation method, preferably, in step (1), the amount of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder is 0.3 to 1 g; in step (2), the amount of antimony acetate, antimony chloride and / or antimony nitrate is 90 to 150 mg; in step (3), the amount of 1,10-phenanthroline is 50 to 150 mg.

[0018] In the above preparation method, preferably, in steps (1) to (4), the dispersion is uniform at room temperature, and the dispersion is uniformly carried out by stirring or ultrasound for 15 to 120 minutes.

[0019] In the above preparation method, preferably, the volume of the fixed volume in step (5) is 200 to 500 mL, and after the fixed volume is reached, the mixture is stirred at 80 to 120° C. for 120 to 360 min.

[0020] In the above preparation method, preferably, the drying temperature in step (6) is 80-120°C.

[0021] In the above preparation method, preferably, the protective gas described in steps (7) to (9) is argon and / or nitrogen; and the gas flow rate of the protective gas is 40 to 250 mL / min.

[0022] In the above preparation method, preferably, in step (7), the calcination temperature is 500-800° C., and the calcination time is 120-480 min.

[0023] In the above preparation method, preferably, the amount of thiourea or sulfur powder used in step (8) is 1 to 3 g, and the amount of the precursor MoS2 / SNGr-Sb used is 0.3 to 1 g.

[0024] In the above preparation method, preferably, the temperature of the sulfurization treatment in step (8) is 400 to 650° C., and the sulfurization treatment time is 120 to 480 min.

[0025] In summary, due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0026] 1. The present invention treats molybdenum disulfide, antimony trisulfide and sulfur-nitrogen co-doped graphene with a thin layer structure in a certain proportion, and synthesizes a bimetallic sulfide / sulfur-nitrogen co-doped graphene sodium ion battery material with a sheet cross-linked structure through a solvent thermal and sulfurization method, which greatly improves the agglomeration phenomenon of molybdenum disulfide and antimony trisulfide; compared with a single sulfide, the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material synthesized by the present invention produces more diversified redox reactions and forms a more stable heterogeneous structure; and the bimetallic sulfide and sulfur-nitrogen co-doped graphene achieve a good synergistic effect, which can well maintain the cycle stability of the material and increase the sodium storage capacity of the material, so that the specific capacity, rate performance and cycle stability of the composite material are improved.

[0027] 2. Since the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material synthesized by the present invention has a sheet cross-linked structure, it is not only conducive to the insertion / extraction reaction of sodium ions, but also can provide a fast transmission channel for ions, and can also prevent molybdenum disulfide and antimony trisulfide from easily collapsing in the cycle process, which helps to increase the sodium storage capacity and enhance the structural stability of the material, so that the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material synthesized by the present invention has a higher specific capacity and very excellent cycle stability. In addition, it can be seen from the CV test that as the scan rate increases from 0.1mV s-1 Increase to 1mV s -1 The pseudocapacitive storage ratio of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material gradually increases, and at different scanning rates, the contribution of the pseudocapacitance is the main one, which is conducive to rapid charging and discharging, indicating that the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material prepared in this application has good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 In the figure, a is the XRD pattern of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material; b is the XPS pattern of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material.

[0029] Figure 2 In the figure, a is the SEM image of molybdenum disulfide (MoS2) alone; b is the SEM image of antimony trisulfide (Sb2S3) alone; c is the SEM image of molybdenum disulfide / sulfur and nitrogen co-doped graphene composite material (MoS2 / SNGr); d is the SEM image of antimony trisulfide / sulfur and nitrogen co-doped graphene composite material (Sb2S3 / SNGr); ef is the SEM image of bimetallic sulfide / sulfur and nitrogen co-doped graphene composite material.

[0030] Figure 3 wherein a is molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur-nitrogen co-doped graphene, antimony trisulfide / sulfur-nitrogen co-doped graphene, and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention at a current of 0.5Ag -1 a is the cycle performance curve of molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur and nitrogen co-doped graphene, antimony trisulfide / sulfur and nitrogen co-doped graphene and the bimetallic sulfide / sulfur and nitrogen co-doped graphene composite material of the present invention at different current sizes; c is the cycle performance curve of the bimetallic sulfide / sulfur and nitrogen co-doped graphene composite material when the current size is 2Ag-1.

[0031] Figure 4 In the figure, a is the CV curve of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material at different scan rates; b is the relationship between the logarithm of the peak current (i) and the logarithm of the scan rate (v); c is the capacitance contribution rate of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material at different scan rates; d is the capacitance contribution rate of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material at 0.6 mV s -1 Capacitive contribution and diffusion contribution of charge storage in bimetallic sulfide / sulfur-nitrogen co-doped graphene composites under scanning. DETAILED DESCRIPTION

[0032] In order to express the present invention more clearly, the present invention is further described below through specific examples.

[0033] 1. Preparation Example

[0034] Example 1

[0035] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0036] (1) Weighing 0.3 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, in which sulfur-nitrogen co-doped graphene accounts for 8%, adding 30 mL of deionized water, and magnetically stirring at room temperature for 15 min to form a uniformly dispersed solution A;

[0037] (2) Weigh 90 mg of antimony acetate, add 50 mL of deionized water, and stir magnetically at room temperature for 15 min to form a uniformly dispersed solution B;

[0038] (3) Weighing 50 mg of 1,10-phenanthroline, adding it to a mixture of 50 mL of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; magnetically stirring at room temperature for 15 minutes to form a uniformly dispersed solution C;

[0039] (4) adding solution B to solution C and magnetically stirring for 15 min at room temperature to form a uniformly dispersed solution D;

[0040] (5) Solution A was added to solution D, and a certain volume of deionized water was added to make the volume 200 mL. The solution was magnetically stirred at 80° C. for 120 min, and finally a solution E with a residual volume of 30 mL was formed.

[0041] (6) drying solution E in an oven at 90° C. to obtain a solid powder;

[0042] (7) placing the dried solid powder in a tube furnace, introducing argon gas at a gas flow rate of 60 mL / min, calcining at 600° C. for 120 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0043] (8) Weigh 1 g of thiourea and 0.3 g of the precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0044] (9) introducing argon gas at a gas flow rate of 60 mL / min, performing a sulfurization treatment at 400° C. for 120 min, and then naturally cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr.

[0045] Example 2

[0046] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0047] (1) Weigh 0.3 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, add 30 mL of ethanol, and stir magnetically for 15 min at room temperature to form a uniformly dispersed solution A; in the molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, sulfur-nitrogen co-doped graphene accounts for 10%

[0048] (2) Weigh 100 mg of antimony acetate, add 50 mL of a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; perform ultrasonic treatment at room temperature for 15 min to form a uniformly dispersed solution B;

[0049] (3) Weighing 90 mg of 1,10-phenanthroline, adding it to a mixture of 50 mL of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; ultrasonicating at room temperature for 15 minutes to form a uniformly dispersed solution C;

[0050] (4) Solution B was transferred into solution C and ultrasonically stirred at room temperature for 15 min to form a uniformly dispersed solution D;

[0051] (5) Solution A was added to solution D, and a certain volume of deionized water was added to make the volume 300 mL. The solution was magnetically stirred at 90° C. for 150 min, and finally a solution E with a residual volume of 30 mL was formed;

[0052] (6) drying solution E in an oven at 80° C. to obtain a solid powder;

[0053] (7) placing the dried solid powder in a tube furnace, introducing argon gas at a gas flow rate of 40 mL / min, calcining at 500 ° C for 480 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0054] (8) Weigh 3 g of thiourea and 1 g of the precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0055] (9) introducing argon gas at a gas flow rate of 40 mL / min, performing a sulfurization treatment at 400° C. for 480 min, and then naturally cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr.

[0056] Example 3

[0057] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0058] (1) Weighing 0.3 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, in which sulfur-nitrogen co-doped graphene accounts for 8%, adding 30 mL of deionized water, and magnetically stirring at room temperature for 30 min to form a uniformly dispersed solution A;

[0059] (2) Weigh 150 mg of antimony acetate, add 50 mL of deionized water, and stir magnetically at room temperature for 30 min to form a uniformly dispersed solution B;

[0060] (3) Weighing 100 mg of 1,10-phenanthroline, adding it to 50 mL of a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; magnetically stirring at room temperature for 30 minutes to form a uniformly dispersed solution C;

[0061] (4) Solution B was transferred into solution C and magnetically stirred at room temperature for 30 min to form a uniformly dispersed solution D;

[0062] (5) Solution A was added to solution D, and a certain volume of ethanol was added to make the volume 400 mL. The solution was magnetically stirred at 80°C for 180 min, and finally a solution E with a residual volume of 30 mL was formed;

[0063] (6) drying solution E in an oven at 90° C. to obtain a solid powder;

[0064] (7) placing the dried solid powder in a tube furnace, introducing argon gas at a gas flow rate of 100 mL / min, calcining at 600° C. for 420 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0065] (8) Weigh 1 g of thiourea and 0.5 g of the precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0066] (9) introducing argon gas at a gas flow rate of 100 mL / min, performing a sulfurization treatment at 400° C. for 420 min, and then naturally cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNG.

[0067] Example 4

[0068] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0069] (1) Weighing 0.3 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, in which sulfur-nitrogen co-doped graphene accounts for 15%, adding 30 mL of deionized water, and magnetically stirring at room temperature for 60 min to form a uniformly dispersed solution A;

[0070] (2) Weigh 90 mg of antimony acetate, add 50 mL of deionized water, and stir magnetically at room temperature for 60 min to form a uniformly dispersed solution B;

[0071] (3) Weighing 150 mg of 1,10-phenanthroline, adding it to 50 mL of a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; stirring the mixture magnetically at room temperature for 60 minutes to form a uniformly dispersed solution C;

[0072] (4) adding solution B to solution C and magnetically stirring for 15 min at room temperature to form a uniformly dispersed solution D;

[0073] (5) Solution A was added to solution D, and a certain volume of deionized water was added to make the volume 500 mL. The solution was magnetically stirred at 120° C. for 240 min, and finally a solution E with a residual volume of 30 mL was formed.

[0074] (6) drying the solution E in an oven at 120° C. to obtain a solid powder;

[0075] (7) placing the dried solid powder in a tube furnace, introducing nitrogen at a gas flow rate of 150 mL / min, calcining at 800 ° C for 360 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0076] (8) Weigh 1.5 g of thiourea and 1 g of the precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0077] (9) nitrogen gas is introduced at a gas flow rate of 150 mL / min, sulfurization treatment is carried out at 500° C. for 360 min, and then naturally cooled to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr.

[0078] Example 5

[0079] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0080] (1) Weighing 0.3 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, in which sulfur-nitrogen co-doped graphene accounts for 8%, adding 30 mL of deionized water, and magnetically stirring at room temperature for 90 min to form a uniformly dispersed solution A;

[0081] (2) Weigh 90 mg of antimony nitrate, add 50 mL of deionized water, and stir magnetically at room temperature for 90 min to form a uniformly dispersed solution B;

[0082] (3) Weighing 50 mg of 1,10-phenanthroline, adding it to 50 mL of a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; magnetically stirring at room temperature for 90 minutes to form a uniformly dispersed solution C;

[0083] (4) adding solution B to solution C and magnetically stirring for 15 min at room temperature to form a uniformly dispersed solution D;

[0084] (5) Solution A was added to solution D, and a certain volume of deionized water was added to make the volume 200 mL. The solution was magnetically stirred at 80°C for 300 min, and finally a solution E with a residual volume of 30 mL was formed;

[0085] (6) drying solution E in an oven at 90° C. to obtain a solid powder;

[0086] (7) placing the dried solid powder in a tube furnace, introducing argon gas at a gas flow rate of 200 mL / min, calcining at 800° C. for 300 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0087] (8) Weigh 1.5 g of thiourea and 0.3 g of the precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0088] (9) introducing argon gas at a gas flow rate of 200 mL / min, performing a sulfurization treatment at 400° C. for 300 min, and then naturally cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr.

[0089] Example 6

[0090] This embodiment prepares a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr, comprising the following steps:

[0091] (1) Weigh 1 g of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, wherein the sulfur-nitrogen co-doped graphene accounts for 15% of the molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, measure 30 mL of deionized water, and stir magnetically for 120 min at room temperature to form a uniformly dispersed solution A;

[0092] (2) Weigh 90 mg of antimony chloride, add 50 mL of deionized water, and stir magnetically at room temperature for 120 min to form a uniformly dispersed solution B;

[0093] (3) Weighing 50 mg of 1,10-phenanthroline, adding it to 50 mL of a mixture of ethanol and deionized water, wherein the volume ratio of ethanol to deionized water in the mixture is 1:1; magnetically stirring at room temperature for 120 min to form a uniformly dispersed solution C;

[0094] (4) adding solution B to solution C and magnetically stirring for 120 min at room temperature to form a uniformly dispersed solution D;

[0095] (5) Solution A was added to solution D, and a certain volume of deionized water was added to make the volume 200 mL. The solution was magnetically stirred at 80°C for 360 min, and finally a solution E with a residual volume of 30 mL was formed;

[0096] (6) drying solution E in an oven at 90° C. to obtain a solid powder;

[0097] (7) placing the dried solid powder in a tube furnace, introducing argon gas at a gas flow rate of 250 mL / min, calcining at 700 ° C for 180 min, and naturally cooling to room temperature after calcination to obtain the precursor MoS2 / SNGr-Sb;

[0098] (8) Weigh 1 g of sulfur powder and 0.3 g of precursor MoS2 / SNGr-Sb, and place them in two separate boats. The boat containing thiourea is placed on the side close to the protective gas.

[0099] (9) introducing argon gas at a gas flow rate of 250 mL / min, performing a sulfurization treatment at 400° C. for 180 min, and then naturally cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material MoS2 / Sb2S3 / SNGr.

[0100] 2. Performance Test

[0101] 1. Confirmation of the compound.

[0102] XRD and XPS scanning were performed on the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite materials obtained in Examples 1-6. The obtained XRD patterns and XPS patterns were as follows: Figure 1 As shown in Figures a and b. From the XRD graph, it can be seen that the (101), (110) and (113) peaks of MoS2 and the (310), (211), (151) and (132) peaks of Sb2S3 correspond to the standard PDF cards of MoS2 (PDF#17-0744) and Sb2S3 (PDF#42-1393), indicating that the method of the present invention successfully prepares the MoS2 / Sb2S3 / SNGr composite material. From the XPS graph, it can be seen that the full spectrum of MoS2 / Sb2S3 / SNGr shows the presence of Mo, Sb, S, N and C.

[0103] 2. Scanning electron microscopy analysis.

[0104] Molybdenum disulfide (MoS2), antimony trisulfide (Sb2S3), molybdenum disulfide / sulfur and nitrogen co-doped graphene composite material (MoS2 / SNGr), antimony trisulfide / sulfur and nitrogen co-doped graphene composite material (Sb2S3 / SNGr), and bimetallic sulfide / sulfur and nitrogen co-doped graphene composite material (MoS2 / Sb2S3 / SNGr) obtained in Examples 1-6 were analyzed by scanning electron microscopy. The obtained SEM images are shown in FIG. Figure 2 shown.

[0105] Among them, a is the SEM image of molybdenum disulfide (MoS2) alone; b is the SEM image of antimony trisulfide (Sb2S3) alone; c is the SEM image of molybdenum disulfide / sulfur and nitrogen co-doped graphene composite material (MoS2 / SNGr); d is the SEM image of antimony trisulfide / sulfur and nitrogen co-doped graphene composite material (Sb2S3 / SNGr); ef is the SEM image of bimetallic sulfide / sulfur and nitrogen co-doped graphene composite material.

[0106] Figure 2 The results show that Figure 2 a and Figure 2 The separate MoS2 and SbS2 in b have serious agglomeration phenomenon. The addition of sulfur and nitrogen co-doped graphene helps to alleviate the agglomeration of MoS2 and SbS2. However, some of them are still in the agglomeration state, such as Figure 2 c and Figure 2 As shown in d; the composite material synthesized by MoS2, SbS3 and thin-layer sulfur-nitrogen co-doped graphene has a cross-linked sheet structure. Figure 2 e and Figure 2 As shown in FIG. 5 , the agglomeration phenomenon of molybdenum disulfide and antimony trisulfide is greatly improved, forming a stable network structure, which will be beneficial to improving the electrochemical properties of the material.

[0107] 3. Cycle performance test

[0108] Using the method in the prior art, molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur-nitrogen co-doped graphene, antimony trisulfide / sulfur-nitrogen co-doped graphene and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention are respectively used as sodium ion negative electrode materials, and are made into sodium ion batteries. Then, the batteries made of different negative electrode materials are respectively tested for cycle performance. The test results are as follows: Figure 3 shown.

[0109] Figure 3 wherein a is molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur-nitrogen co-doped graphene, antimony trisulfide / sulfur-nitrogen co-doped graphene, and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention at a current of 0.5Ag -1 The cycle performance curve of the present invention is as follows; it can be seen from the figure that the capacity of antimony trisulfide alone is low and the cycle stability is poor, the capacity of molybdenum disulfide alone is low, and after sulfur-nitrogen co-doped graphene is added to molybdenum disulfide and antimony trisulfide, the capacity and cycle stability of the material are improved, and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material synthesized by the present invention has a higher specific capacity and very excellent cycle stability, this is because the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material has a lamellar cross-linked structure, which is not only conducive to the insertion / extraction reaction of sodium ions, and can provide a fast transmission channel for ions, but also can prevent molybdenum disulfide and antimony trisulfide from easily collapsing in the cycle process, which helps to increase the sodium storage capacity and enhance the structural stability of the material.

[0110] Figure 3 In the figure, b is the rate performance curve of molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur-nitrogen co-doped graphene, antimony trisulfide / sulfur-nitrogen co-doped graphene and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention at different current sizes; it can be seen from the figure that compared with other materials, the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention has higher specific capacity and better rate performance at different current densities, because the cross-linked network structure of the sheets can increase the sodium storage capacity and enhance the structural stability of the material.

[0111] Figure 3 In the figure, c is the cycle performance curve of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material at a current of 2Ag-1. The results show that the composite material synthesized by the present invention has a stable heterostructure formed by sulfur-nitrogen co-doped graphene, molybdenum disulfide and antimony trisulfide, and the bimetallic sulfide and graphene achieve good synergy, which can well maintain the cycle stability of the material and increase the sodium storage capacity of the material, thereby obtaining good electrochemical performance.

[0112] The specific capacity comparison of molybdenum disulfide, antimony trisulfide, molybdenum disulfide / sulfur-nitrogen co-doped graphene, antimony trisulfide / sulfur-nitrogen co-doped graphene and the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material of the present invention at different current sizes is shown in Table 1.

[0113] Table 1

[0114]

[0115] It can be concluded from Table 1 that the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material prepared by the present invention has a higher specific capacity at different current sizes, which indicates that the lamellar cross-linked structure of the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material helps to increase the sodium storage capacity of the material and can improve the specific capacity of the material.

[0116] 4. CV test

[0117] The battery made of bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material as sodium ion negative electrode material was tested by CV at different scan rates. The test results are as follows: Figure 4 shown.

[0118] in, Figure 4 a is the CV curves of bimetallic sulfide / sulfur-nitrogen co-doped graphene composites at different scanning rates; Figure 4 b Relationship between the logarithm of the peak current (i) and the logarithm of the scan rate (v); Figure 4 c is the capacitance contribution rate of bimetallic sulfide / sulfur-nitrogen co-doped graphene composites at different scanning rates; Figure 4 d at 0.6mV s -1 Capacitive contribution and diffusion contribution of charge storage in bimetallic sulfide / sulfur-nitrogen co-doped graphene composites under scanning.

[0119] The results show that as the scan rate increases from 0.1 mV s -1 Increase to 1mV s -1 The pseudocapacitive storage ratio of bimetallic sulfide / sulfur-nitrogen co-doped graphene composites gradually increases. The increase in pseudocapacitive storage ratio is related to the diffusion rate of ions, indicating that the sheet cross-linked structure of bimetallic sulfide / sulfur-nitrogen co-doped graphene composites promotes the Na + diffusion, solving the problem of Na + The problem of slow insertion / extraction. However, at different scan rates, the contribution of pseudocapacitance is the main one, which is conducive to fast charging and discharging, indicating that the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material prepared in this application has good rate performance.

[0120] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A sodium ion battery material having a sheet cross-linked structure, characterized in that: The sodium ion battery material is a bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material with a molecular formula of MoS2 / Sb2S3 / SNGr. The sodium ion battery material has a mutually cross-linked sheet structure.

2. The method for preparing a sodium ion battery material having a sheet cross-linked structure according to claim 1, characterized in that: The steps include: (1) taking molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder, adding deionized water and / or ethanol, and dispersing evenly to obtain solution A; (2) taking antimony acetate, antimony chloride and / or antimony nitrate, adding them to deionized water or a mixture of ethanol and deionized water, and dispersing them evenly to obtain solution B; (3) taking 1,10-phenanthroline, adding a mixture of ethanol and deionized water, and dispersing the mixture evenly to obtain a solution C; (4) adding the solution B obtained in step (2) to the solution C obtained in step (3) and dispersing them evenly to form a solution D; (5) adding the solution A obtained in step (1) above to the solution D obtained in step (4), and adding deionized water and / or ethanol to make up the volume to form a solution E; (6) drying solution E to obtain a solid powder; (7) placing the dried solid powder in a tube furnace, introducing a protective gas, calcining under a protective gas environment, and cooling to room temperature after the calcination to obtain a precursor MoS2 / SNGr-Sb; (8) placing thiourea or sulfur powder in a first calcined boat, placing the precursor MoS2 / SNGr-Sb in a second calcined boat, placing the first calcined boat and the second calcined boat in a tube furnace, wherein the first calcined boat is located on the side close to the protective gas introduction; (9) introducing a protective gas, performing a sulfurization treatment in the protective gas, and then cooling to room temperature to obtain the bimetallic sulfide / sulfur-nitrogen co-doped graphene composite material.

3. The preparation method according to claim 2, characterized in that: In step (1), the amount of molybdenum disulfide / sulfur-nitrogen co-doped graphene composite material powder is 0.3 to 1 g; in step (2), the amount of antimony acetate, antimony chloride and / or antimony nitrate is 90 to 150 mg; in step (3), the amount of 1,10-phenanthroline is 50 to 150 mg.

4. The preparation method according to claim 2, characterized in that: In steps (1) to (4), the dispersion is uniform at room temperature, and the dispersion is uniformly carried out by stirring or ultrasound for 15 to 120 minutes.

5. The preparation method according to claim 2, characterized in that: In step (5), the volume is adjusted to 200-500 mL, and after adjusting the volume, the mixture is stirred at 80-120° C. for 120-360 min.

6. The preparation method according to claim 2, characterized in that: The drying temperature in step (6) is 80-120°C.

7. The preparation method according to claim 2, characterized in that: The protective gas described in steps (7)-(9) is argon and / or nitrogen; the gas flow rate of the protective gas is 40 to 250 mL / min.

8. The preparation method according to claim 2, characterized in that: In step (7), the calcination temperature is 500-800° C. and the calcination time is 120-480 min.

9. The preparation method according to claim 2, characterized in that: In step (8), the amount of thiourea or sulfur powder used is 1 to 3 g, and the amount of the precursor MoS2 / SNGr-Sb used is 0.3 to 1 g.

10. The preparation method according to claim 2, characterized in that: In step (8), the temperature of the vulcanization treatment is 400 to 650° C., and the vulcanization treatment time is 120 to 480 min.

Citation Information

Cited By

  • Negative electrode composite material and preparation method thereof, negative electrode pole piece and battery

    CN121054647A